ASED-MO CALCULATIONS OF UNSYMMETRICAL 3-COORDINATE CUN2S AND 4-COORDINATE CUN2S2 CORES - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1992)
The molecular orbitals of [diammine(dimethyl sulphide)(methylthiolate)copper (II)]+ and the three-coordinate complex ion without the dimethyl sulphide ligand [diammine(methylthiolato)copper(II)]+ were calculated by the ASED-MO method and are reported for the C1 point group. The molecular orbitals a37 and a38 of the four-coordinate complex ion and a17 and a18 of the three-coordinate complex ion are of sigma symmetry with respect to the Cu-S(methylthiolate) bond. Transitions from the molecular orbitals a37 or a17 at 16.577 and 16.504 cm-1, respectively, in the four- and three-coordinate structures to the singly occupied molecular orbital of that complex ion are calculated to have oscillator strengths of ca 0.044 and 0.048. respectively. The singly occupied molecular orbital has about 15% 3d(xy)(Cu) atomic orbital character and about 73% 3p(x)(S(methylthiolate)) atomic orbital character.
Keywords: TRANSITION-METAL SERIES; ELECTRONIC-STRUCTURE; PLASTOCYANIN; OXIDES